Magnetic resonance relaxation at ultra low temperatures - Peat, David T. (2015)
The focus of this thesis is to produce highly polarised Nuclear Magnetic Resonance (NMR) samples for use in vivo applications. This work focuses on using the brute force method to polarise relevant molecules, for example, 13C labelled pyruvic acid and 13C labelled sodium acetate. The brute force method uses the Boltzmann distribution to polarise a sample by exposing it to large magnetic fields, 15 T, and ultra-low temperatures, ~20 mK. The disadvantage of using this method is the long polarisation time. To counteract the long relaxation times, two sets of relaxation agents were assessed: paramagnetic lanthanides and nanoparticles. Chelated gadolinium is routinely used as a spin-lattice, T1, contrast agent in clinical Magnetic Resonance Imaging (MRI). It is known that when the electron spin flip time is similar to the Larmor frequency, the T1¬ time of the nuclei is reduced. Each lanthanide has a different electron spin flip time, therefore, one lanthanide may be effective at low temperatures. Unfortunately the lanthanides do not prove to be efficient in the millikelvin regime, where the brute force method is at its most effective, so the lanthanides are of limited use. Metals are known to have short T1 times in the millikelvin regime due to the Korringa effect. The conduction electrons of the metal can contribute or absorb energy from nuclei, resulting in a reduction of the T1 of relevant molecules. By having a strong interaction between conduction electrons and the nuclei of interest, it could be possible to reduce the T1¬ of any nuclei of interest. To maximise the contact between the metals and the nuclei, metal nanoparticles were used. Copper and platinum nanoparticle samples are shown to enhance the relaxation rate of nearby protons, however, aluminium and silver nanoparticle samples, which are also expected to be effective, are not. This contradicts the idea that the Korringa effect is the only relaxation mechanism which relaxes the nuclei. The magnetic properties of nanoparticles can be different from their bulk counterpart, therefore, could be contributing to the relaxation of nearby nuclei. It would therefore be advantageous to study the nanoparticle’s magnetisation in a Superconducting Quantum Interference Device (SQUID). Unfortunately, the interpretation of the magnetisation becomes very complicated, as the nanoparticles can react with the solvents. These reactions can result in a 1000-fold increase in the magnetisation of the sample. With the limited magnetic data collected in this work, it is difficult to correlate the nanoparticles magnetic properties with their effectiveness as a T1 relaxation agent.